Preliminary Study of S100B and Sema3A Expression Patterns in Regenerating Muscle Implicates P75-Expressing Terminal Schwann Cells and Muscle Satellite Cells in Neuromuscular Junction Restoration - Daneshvar, Nasibeh; Anderson, Judy E. (Frontiers in Cell and Developmental Biology, 2022)
Terminal Schwann cells (TSCs) help regulate the formation, maintenance, function, and repair of neuromuscular junctions (NMJs) and axon guidance after muscle injury. Premature activation of muscle satellite cells (SCs), induced by isosorbide dinitrate (ISDN) before injury, accelerates myogenic regeneration, disrupts NMJ remodeling and maturation, and decreases Sema3A-induced neuro-repulsion and time-dependent changes in S100B. Here, to study effects of premature SC activation on TSCs and SCs, both expressing P75 nerve-growth factor receptor, in situ hybridization was used to identify transcripts of S100B and Sema3A, and the number, intensity, and diameter of expression sites was analyzed. The number of sites/field expressing S100B and Sema3A increased with regeneration time (both p<0.001). Expression-site intensity (S100B) and diameter (S100B and Sema3A) decreased during regeneration (p=0.005; and p<0.05, p=0.006, respectively). P75 protein colocalized with a subset of S100B and Sema3A expression sites. Principal component analyses of gene expression, protein levels, and histological variables (fiber diameter, vascular density) in control and ISDN-pretreated groups explained 83% and 64% of dataset variance, respectively. A very strong loading coefficient for colocalization of P75 protein with S100B and Sema3A mRNAs (0.91) in control regenerating muscle, dropped markedly during regeneration disrupted by premature SC activation (-0.10 in Factor 1 to 0.55 in Factor 3). These findings strongly implicate the triple-expression profile by TSCs and/or SCs as a strong correlate of the important synchrony of muscle and nerve regeneration after muscle tissue injury. Results have potential to focus future research on the complex interplay of TSCs and SCs in neuromuscular tissue repair, and help promote effective function after traumatic muscle injury.